A COMPARATIVE STUDY OF MAJOR RELIGIONS' PERSPECTIVES ON HUMAN RIGHTS IN INDONESIA: INSIGHTS FROM ISLAM, CHRISTIANITY, HINDUISM, AND BUDDHISM: Studi Komparatif Pandangan Agama-agama Besar di Indonesia tentang Hak Asasi Manusia: Perspektif Islam, Kristen, Hindu, dan Buddha - Ekowati, Endang (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study explores the comparative perspectives on human rights within the teachings of four major religions in Indonesia: Islam, Christianity, Hinduism, and Buddhism. Against the backdrop of Indonesia’s rich religious diversity and ongoing discourse on human rights, this research examines how each religion interprets and addresses fundamental human rights issues. The research addresses the question of how these religious doctrines align or diverge in their approach to human rights principles, particularly concerning freedom, equality, and social justice. Using a qualitative methodology, the study draws upon religious texts, interviews with religious leaders, and scholarly literature to analyze the foundational views and teachings of each religion on human rights. Findings indicate that while there are significant commonalities in advocating for human dignity and moral responsibilities, each religion emphasizes distinct principles that reflect its unique doctrines. The conclusion underscores the potential of interfaith dialogue to bridge differences and promote a more inclusive understanding of human rights in a pluralistic society. This study contributes to the broader discourse on religion and human rights in multicultural contexts like Indonesia.